Edukasi Sekolah Ramah Anak Sinergi Pendidikan Karakter, Kesadaran Hukum, dan Literasi Digital dalam Membentuk Lingkungan Bebas Bullying di SD - Abshor, Devy Aufia; Arina Novitasari; Avira Budianita (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
This community service was carried out in January 2026 which aims to improve the understanding and skills of teachers and students in implementing positive character values, strengthening digital literacy and raising awareness of the importance of legal protection for children so as to create a school culture that is safe, orderly, and respects the rights of every individual. In order to achieve this goal, the community service educates students and teachers about child-friendly schools that synergize character education, legal awareness, and digital literacy in creating a bullying-free environment in elementary schools. Bullying is a problem faced at SD Aisyiyah Multilingual Darussalam Kudus, based on observations and interviews, there are still student behaviors that cause discomfort to other students both verbally, socially, and non-verbally; lack of knowledge about the rules; and the weak child-friendly school culture. This community service uses the PAR (Participatory Action Research) method and test questions. This community service has two activities, namely an inspirational class with 18 students, and a workshop with 14 teachers. The results of the pretest and post-test showed an increase after education with an average of 18.3% of students and 18% of teachers. This improvement is proven by the active participation of students and teachers during role playing, project creation, case studies, and Q&A sessions.